At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To solve for \(x\) and \(y\) given the equation \((5y - 2) + i(3x - y) = 3 - 7i\), we need to equate the real and imaginary parts separately. Let's break it down step-by-step:
1. Identify the real and imaginary parts:
[tex]\[ (5y - 2) + i(3x - y) = 3 - 7i \][/tex]
2. Equate the real parts:
[tex]\[ 5y - 2 = 3 \][/tex]
Solve for \(y\):
[tex]\[ 5y - 2 = 3 \\ 5y = 5 \\ y = 1 \][/tex]
3. Equate the imaginary parts:
[tex]\[ 3x - y = -7 \][/tex]
Substitute \(y = 1\):
[tex]\[ 3x - 1 = -7 \\ 3x = -6 \\ x = -2 \][/tex]
Hence, the values of \(x\) and \(y\) that satisfy the equation \((5y - 2) + i(3x - y) = 3 - 7i\) are:
[tex]\[ x = -2 \quad \text{and} \quad y = 1 \][/tex]
1. Identify the real and imaginary parts:
[tex]\[ (5y - 2) + i(3x - y) = 3 - 7i \][/tex]
2. Equate the real parts:
[tex]\[ 5y - 2 = 3 \][/tex]
Solve for \(y\):
[tex]\[ 5y - 2 = 3 \\ 5y = 5 \\ y = 1 \][/tex]
3. Equate the imaginary parts:
[tex]\[ 3x - y = -7 \][/tex]
Substitute \(y = 1\):
[tex]\[ 3x - 1 = -7 \\ 3x = -6 \\ x = -2 \][/tex]
Hence, the values of \(x\) and \(y\) that satisfy the equation \((5y - 2) + i(3x - y) = 3 - 7i\) are:
[tex]\[ x = -2 \quad \text{and} \quad y = 1 \][/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.